KINERJA GURU PAI DALAM PELAKSANAAN PEMBELAJARAN DI MTS SE-KOTA PAGAR ALAM - Nurfarida Nurfarida (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2020)
Performance of Teachers  PAI In Implementation Learning  In MTs Se-Pagar Alam (Study Between  Master certifica- tion  with a  Non-Certified  Teacher). This research  uses  quantitative and  comparative approach.  Population and  sample  in this research  are all teachers  of Islamic Religious Education either certified or not certified in MTs Se-Pagar natural  city which amounts to 31 teachers  of Islamic Education. The data collection technique is done  by using questionnaire method used to ob- tain data about  the performance of Islamic Religious Education teacher, the method of observation is done to know the process of learning by the teacher  in class, the method of documentation is done to obtain data about  the teacher, while the validity test used is the validity test of the correlation  formula product  Moment,  while to test reliabel using Cromach Alpa analysis formula used  in the form of statistical analysis by using t-test formula.  Based  on the result of t-test analysis, there  are significant differ- ences in the performance of teachers  of Islamic Religion certification and non certification